Vulnerability and Adaptive Skills of older People in the Face of Climate Change: a Systematic Review - Navarrete-Valladares, Camila Paz; Sandoval, Jose (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Background: The sustained increase in population aging, under the ongoing climate change, configure new scenarios of social and health risks for the older adult population. However, adaptive capacities can mitigate the impact of structural vulnerabilities through the use of individual and collective coping strategies. Objective: To conduct a systematic review of studies that have reported the relationship between adaptive capacity and vulnerability of older people in the face of climate change. Method: The review followed the guidelines of the PRISMA statement, consulting the Web of Science, Scopus and Scielo databases. In total, 50 empirical studies, in Spanish and English, published between 2010 and 2021, that met the inclusion criteria were reviewed. Results: The predominance of social, individual and community factors associated with vulnerability to climate change was identified, being the most studied morbidity and economic constraints. Regarding coping strategies, behavioral and cultural strategies were predominant. Conclusions: The importance of (re)understanding agency capacity and active aging is highlighted in order to address the various risks associated with climate change.